Descriptive Analysis Testing for Sensory Evaluation (2nd Edition) - Bleibaum Rebecca N (ASTM International, 2020)
Get this fully updated new version featuring a comprehensive overview of the four most widely-used methods of sensory descriptive analysis testing/descriptive analysis methods: consensus/flavor profile; quantitative descriptive analysis (QDA); spectrum; texture profile. Also features two new chapters on free choice profiling and a summary of temporal methods. More than 30 distinguished sensory professionals provide their detailed views of the descriptive methodology covered, including new developments and case studies.